Ferrimagnetic spin-1/2 chain of alternating Ising and Heisenberg spins in arbitrarily oriented magnetic field - Strečka, J.; Hagiwara, M.; Han, Y.; Kida, T.; Honda, Z.; Ikeda, M. (Condensed Matter Physics, 2012)
The ferrimagnetic spin-1/2 chain composed of alternating Ising and Heisenberg spins in an arbitrarily oriented magnetic field is exactly solved using the spin-rotation transformation and the transfer-matrix method. It is shown that the low-temperature magnetization process depends basically on a spatial orientation of the magnetic field. A sharp stepwise magnetization curve with a marked intermediate plateau, which emerges for the magnetic field applied along the easy-axis direction of the Ising spins, becomes smoother and the intermediate plateau shrinks if the external field is tilted from the easy-axis direction. The magnetization curve of a polycrystalline system is also calculated by performing powder averaging of the derived magnetization formula. The proposed spin-chain model brings an insight into high-field magnetization data of 3d-4f bimetallic polymeric compound Dy(NO₃)(DMSO)₂Cu(opba)(DMSO)₂, which provides an interesting experimental realization of the ferrimagnetic chain composed of two different but regularly alternating spin-1/2 magnetic ions Dy³+ and Cu²+ that are reasonably approximated by the notion of Ising and Heisenberg spins, respectively. Феримагнiтний спiн-1/2 ланцюжок, який складається з почергових Гайзенбергових та Iзингових спiнiв у довiльно орiєнтованому магнiтному полi, розв’язується точно, використовуючи перетворення повороту спiнiв та метод трансфер-матрицi. Показано, що низькотемпературний процес намагнiчення залежить в основному вiд просторової орiєнтацiї магнiтного поля. Гостра сходинкоподiбна форма кривої намагнi-ченостi з помiтним промiжним плато, яке з’являється у магнiтному полi прикладеному вздовж напрямку легкої осi Iзингових спiнiв, стає гладшою та промiжне плато коротшає, якщо зовнiшнє поле вiдхиляється вiд напрямку легкої осi. Крива намагнiченостi полiкристалiчної системи також обчислюється, здiйсню-ючи конфiгурацiйне усереднення отриманої формули для намагнiченостi. Запропонована модель спi-нового ланцюжка дає розумiння намагнiченостi у сильних полях 3d-4f бiметалiчної полiмеpної сполу-ки Dy(NO₃)(DMSO)₂Cu(opba)(DMSO)₂, яка допускає цiкаву експериментальну реалiзацiю феримагнiтного ланцюжка, складеного з двох рiзних, але регулярно змiнних спiн-1/2 магнiтних iонiв Dy³+ and Cu²+, що прийнятно апроксимуються поняттями Iзингових та Гайзенбергових спiнiв, вiдповiдно.